2016
DOI: 10.3233/rnn-150633
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar tDCS as a novel treatment for aphasia? Evidence from behavioral and resting-state functional connectivity data in healthy adults

Abstract: Background Aphasia is an acquired deficit in the ability to communicate through language. Noninvasive neuromodulation offers the potential to boost neural function and recovery, yet the optimal site of neuromodulation for aphasia has yet to be established. The right posterolateral cerebellum is involved in multiple language functions, interconnects with left-hemisphere language cortices, and is crucial for optimization of function and skill acquisition, suggesting that cerebellar neuromodulation could enhance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 81 publications
2
60
1
Order By: Relevance
“…In children and adults who have sustained cerebellar damage, both show deficits in verbal fluency tasks (Baillieux et al, 2010; Riva 1998; Scott et al, 2001). Electrostimulation studies have also revealed changes in tasks of verbal fluency, lexical decision-making, verb generation, and verbal working memory when undergoing TMS and tDCS (Arasanz et al, 2012; Argyropoulos & Muggleton, 2013; Boehringer et al, 2013; Pope & Miall, 2012; Turkeltaub et al, 2016). Examining typical and atypical cerebellar development and its association with linguistic tasks highlights the expanding view of the cerebellum’s role in higher-order cognitive functions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In children and adults who have sustained cerebellar damage, both show deficits in verbal fluency tasks (Baillieux et al, 2010; Riva 1998; Scott et al, 2001). Electrostimulation studies have also revealed changes in tasks of verbal fluency, lexical decision-making, verb generation, and verbal working memory when undergoing TMS and tDCS (Arasanz et al, 2012; Argyropoulos & Muggleton, 2013; Boehringer et al, 2013; Pope & Miall, 2012; Turkeltaub et al, 2016). Examining typical and atypical cerebellar development and its association with linguistic tasks highlights the expanding view of the cerebellum’s role in higher-order cognitive functions.…”
Section: Resultsmentioning
confidence: 99%
“…Several brain stimulation studies, using transcranial magnetic stimulation (TMS) or transcranial direct current stimulation (tDCS), have illustrated the cerebellum’s contribution to linguistic function (Tomlinson, Davis, & Bracewell, 2013; Turkeltaub, Swears, D’Mello, & Stoodley, 2016). Both of these methods work by either enhancing or disrupting neural function under the site of stimulation.…”
Section: Cerebellar Contributions To Language and Its Development: Nementioning
confidence: 99%
“…Contrary to these findings, in a group of healthy subjects, Turkeltaub and collaborators (Turkeltaub, Swears, D'Mello, & Stoodley, 2016) showed that both anodal and cathodal stimulation over the right cerebellum improves word generation but the effects were found using a different task, namely a phonemic fluency task. Following Pope and Miall's suggestion (Pope & Miall, 2014;Pope & Miall, 2012), the authors hypothesized that cerebellar tDCS did not act directly on the language function per se but on the executive control and response selection components required by the generation task (Turkeltaub et al, 2016).…”
mentioning
confidence: 83%
“…Following Pope and Miall's suggestion (Pope & Miall, 2014;Pope & Miall, 2012), the authors hypothesized that cerebellar tDCS did not act directly on the language function per se but on the executive control and response selection components required by the generation task (Turkeltaub et al, 2016).…”
mentioning
confidence: 99%
“…Damage to the right cerebellum has been associated with deficits in a variety of language tasks (e.g., Hassid, 1995; Marien et al, 1996, 2000; Gómez Beldarrain et al, 1997; Fabbro et al, 2004; Baillieux et al, 2010). In addition, cerebellar tDCS studies in healthy individuals provide evidence that right cerebellar tDCS modulates cognitive and language functions such as verb generation (Pope and Miall, 2012), verbal fluency (Turkeltaub et al, 2016), working memory (Boehringer et al, 2013; Macher et al, 2014), and implicit learning (Ferrucci et al, 2013). See Grimaldi et al (2016) for a recent review.…”
Section: Introductionmentioning
confidence: 99%